Physical and mechanical properties of concrete containing hematite as aggregates - Gencel Osman (Science and Engineering of Composite Materials, 2011)
Radiation limits above permission limit have harmful effects on living bodies (i.e., carcinogenic, etc.). Heavyweight concrete is used in facilities such as nuclear power plant and radiotherapy room where radioactive impermeability is required. Aggregate and cement play an essential role in both the shielding performance and the structural behavior of concrete. Concretes with 0% (control), 15%, 30%, 45% and 60% of conventional aggregate replaced by hematite aggregate for each control concrete, were fabricated with 300, 350, 400 and 450 kg/m3cement contents. Water-cement ratio was kept constant at 0.40. In addition to investigation of the mineralogical structure of hematite, physical and mechanical experiments were carried out on the concrete produced. The results show that slump and compressive strength, like other mechanical properties, increase as the hematite aggregate replacement volume increase.